Effect of Co-Contaminant on Denitrification Removal of Nitrate in Drinking Water - KILIÇ, Arzu; BAŞAK, Serden; CIRIK, Kevser; ÖZGÜN, Dilek; AKMAN, Dilek; ÖZDEMİR, Şebnem; ÇINAR, ÖZER (Journal of History Culture and Art Research, 2013)
In recent years, nitrogenous fertilizers used in agriculture, unconscious and without treatment wastewater is discharged led to an increase in groundwater nitrate pollution. In many countries, nitrate concentration in the ground waters used as drinking water source exceeded the maximum allowable concentration of 10 mg/L NO3-N. According to a study, some wells in the Harran Plain contain nitrate as high as 180 mg/L NO3--N and the average concentration for whole plain is 35 mg/L NO3--N (Yesilnacar et al., 2008). Additionally, increased water consumption, unconscious use of fertilizers and pesticides has led to the emergence of co-contaminant in drinking water. Recently, hazardous to human health co-contaminant such as arsenic, pesticides, perchlorate, selenate, chromate, uranium are observed in the nitrate pollution drinking water. There are many processes used for the removal of nitrate. The physicalchemical technologies that can be used for nitrate removal are reverse osmosis, ion exchange and electrodialysis (Alvarez et al., 2007). Important disadvantages of these processes are their poor selectivity, high operation and maintenance costs and the generation of brine wastes after treatment. Consequently, biological treatment processes to convert nitrates to benign dinitrogen gas, could be an interesting alternative for the remediation of groundwater contaminated with nitrates.The aim of this article, effective and cheap method for the removal of nitrate from drinking water biological denitrification is to examine the usability of contaminated drinking water with co-contaminant pollutions.